De Morgan's laws
De Morgan's first law
De Morgan's first law says that not(A or B) is the same as not A and not B and is written as A + B = A.B
If you examine the Venn diagram above, X or Y is anywhere inside the area covered by the two combined circles, so not(X or Y) is the light green area outside of this. If it has to be in the area outside the yellow circle and the area outside the blue circle this describes the same light green area.
De Morgan's second law
De Morgan's second law says that not(A and B) is the same as not A or not B and is written as A.B = A + B
If you examine the Venn diagram above, X and Y is the bright green area in the center, so not(X and Y) is everything outside of this. If something is not X or not Y it can also be anywhere except in the bright green section.
Commutative rules
These allow us to rearrange equations. The two rules are:
X.Y = Y.X
X + Y = Y + X
You can see in the venn diagram above these cover the same area.
Absorption rules
The absorption rules are:
X + (X.Y) = X
If you look at the venn diagram X.Y is the bright green area entirely contained inside X.
X.(X + Y) = X
If a value is in X and in X or Y it can only be in the part of X or Y that is X.
Associative rules
The associative rules are:
X.(Y.Z) = (X.Y).Z
As you can see above, regardless of whether we combine X and Y and then and that result with Z or combine Y and Z and and that result with X the same small green area is defined.
X + (Y + Z) = (X + Y) + Z
Similarly whether we look at the area covered by X or Y and or that result with Z or look at the area reoresented by Y or Z and or that with X we still define the entire area of the three combined circles.
Simplifying boolean expressions
When simplifying boolean expressions you should make one change on each line and specify what rule you are relying on. Each correct application will score a mark even if you go wrong before the final answer.
Let's simplify (A+B).(B+C.(D+D))
= (A+B).(B+C.1) (X+X=1)
= (A+B).(B+C) (X.1=X)
= A.B + A.C + B.B + B.C (Distributive rule)
= A.B + A.C + B + B.C (X.X=X)
= A.B + A.C + B (Absorption rule)
= A.C + B + A.B (Commutative rule)
= A.C + B (Absorption rule)